If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
-(x/2) = 0
-1/2*x = 0 // : -1/2
x = 0
x = 0
| 2x-(2x+9)-6=-4x-6(-9-x)+2 | | U=7x+6b-5+2x-6b+4 | | 4y=120 | | (p^5/p^3)^6 | | 12m=9 | | 3x^2+6y^2=18 | | 5x-11=2(x+2) | | J=11-2.5(1.56) | | Z+-4x=2y | | y^3+2x=x-1 | | (8+2i)(5-9i)= | | -36+4x=12 | | 2x+4y-1=3+y | | 8-8x20/20 | | f(x+8)=2x-4 | | x^2+lnx-1=0 | | 15+5x=40 | | (7/(3a))/(2/5) | | 2x^-5/3y^0 | | (7/(3a))/(2.5) | | x=1/50 | | -(-8)/(-8)-3 | | 2/5x30=-50 | | 2x=1/25 | | 8x+3=3x+9 | | 3(2x+8)=15 | | cosx/3=0 | | -3x+14=23 | | R=-4x-9z+5z-9x+3x-8z | | x*2=1/25 | | 9y^2+1=6x | | (10x^6)(5x^2)= |